Cash support vs. tax incentives: The differential impact of policy interventions on third births in contemporary Hungary. (2nd January 2020) - Spéder, Zsolt; Murinkó, Lívia; Oláh, Livia Sz.
Abstract : Following steep falls in birth rates in Central and Eastern European countries during the economic and institutional restructuring of the early 1990s, governments made substantial efforts to stop or at least reduce the fertility decline. In Hungary, parents with three or more children could benefit from specific new policy measures: the flat-rate child-rearing support paid from the youngest child's third to eighth birthdays (signalling recognition of stay-at-home motherhood) and a redesigned and upgraded tax relief system. However, the success of these policy measures, if any, is difficult to detect in aggregate statistics. Analysing data from the Hungarian Generations and Gender Survey, we rely on event history methods to examine the policies' effects on third birth risks, especially among different socio-economic groups. The results indicate that while the child-rearing support increased third birth risks among the least educated, the generous tax relief had a similar effect for parents with tertiary education.